Knowledge, attitudes and practices of government animal health workers on antibiotic use and antibiotic resistance in Timor-Leste - Ting, Shawn; Pereira, Abrao; Alves, Amalia; Vong da Silva, Paulo Gabriel; Dos Santos, Cristibela; Davis, Steven; Sidjabat, Hanna E.; Yan, Jennifer; Francis, Joshua R.; Bendita da Costa Jong, Joanita; Barnes, Tamsin S. (Frontiers in Veterinary Science, 2022)
Introduction Antibiotic resistance is a global health threat, and there is growing concern on the inappropriate use of antibiotics in the livestock sector especially in low and middle income countries. The purpose of the study was to understand the knowledge, attitudes and practices on antibiotic use and antibiotic resistance of government animal health workers in Timor-Leste. Method A cross-sectional survey using a census approach was conducted between August 2021 and January 2022 focusing on government animal health workers involved in field work and access to antibiotics. Interviews were face-to-face in the local Tetun language. Descriptive and regression analysis informed by causal diagrams were performed. Result The study found poor knowledge of antibiotics among participants, with only 8.0% (13/162) able to correctly answer questions on how antibiotics worked. Knowledge of antibiotic resistance was poor as only 29.0% (47/162) of participants had heard of antibiotic resistance and were able to accurately identify that it made antibiotics less effective. Knowledge of antibiotics and knowledge of antibiotic resistance were crudely associated with being a veterinary technician and having university education. Attitude scores were positively influenced by knowledge of antibiotics and antibiotic resistance. Antibiotics were most commonly used in pigs, cattle and buffalo, with oxytetracycline being the most commonly used antibiotics in pigs and chicken. However, most participants reported a lack in supply of this antibiotic (137/162, 78.4%) and other antibiotics. Empiric use of antibiotics in sick animals was common, and some participants used antibiotics for parasitic diseases. Less than a fifth of participants reported ever using human antibiotics, and use of antibiotics for growth promotion was uncommon. Conclusion There is a need to develop Timor-Leste specific treatment guidelines, strengthen veterinary diagnostic support, improve antibiotic procurement, and develop training programs to address knowledge gaps and poor practices found in this study.